2018
DOI: 10.1590/s0004-2803.201800000-74
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in the Brazilian Public Health Care System: Burden of Disease

Abstract: BACKGROUND: Infection by hepatitis C virus is one of the leading causes of chronic hepatitis C and cause severe burden for patients, families and the health care system. OBJECTIVE: The aims of this research were to assess the severity of liver fibrosis, comorbidities and complications of hepatitis C virus; to examine health-related quality of life (HRQoL), productivity loss and resource use and costs in a sample of Brazilian chronic hepatitis C, genotype 1, patients. METHODS: This was a cross-sectional mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
5
1
2
Order By: Relevance
“…The best form of segment for these patients who obtain SVR is still a topic that leaves a gap, due to the variability in the presentation of residual liver disease, both in the laboratory aspect and in imaging methods. In our study, the distribution of the degree of fibrosis among the patients evaluated before starting treatment was F0-F1 15.4%, F2 15.4%, F3 23.1%, and F4 46.2%, compared to a Brazilian study Castelo et al (54), involving 313 monitored in the public health system, where 42.8% of patients who underwent TE had cirrhosis. In ratification of our findings, in the study conducted by Loo et al (55) of the 411 patients evaluated at the beginning of treatment, 47.6% had basal fibrosis from F3 to F4.…”
Section: Discussioncontrasting
confidence: 59%
“…The best form of segment for these patients who obtain SVR is still a topic that leaves a gap, due to the variability in the presentation of residual liver disease, both in the laboratory aspect and in imaging methods. In our study, the distribution of the degree of fibrosis among the patients evaluated before starting treatment was F0-F1 15.4%, F2 15.4%, F3 23.1%, and F4 46.2%, compared to a Brazilian study Castelo et al (54), involving 313 monitored in the public health system, where 42.8% of patients who underwent TE had cirrhosis. In ratification of our findings, in the study conducted by Loo et al (55) of the 411 patients evaluated at the beginning of treatment, 47.6% had basal fibrosis from F3 to F4.…”
Section: Discussioncontrasting
confidence: 59%
“…Patients with genotypes 2 and 3 obtained the lowest SVR rates (92.2% and 90.6%, respectively) and were 1.5 and 2.8 more likely to not have SVR, respectively, when compared to genotype 1a and 1b, a finding that has been confirmed in other studies [19, 20, 21, 22, 23, 24, 25] .. Genotype 4 had an SVR of 97.6%, an excellent result, but the difference cannot be established as significant due to the small number of cases. Ferreira and collaborators evaluated 296 patients in the South region, obtaining SVR rates of 92% [16] . Another study including 1,002 patients treated for HCV, with genotypes 1, 2 and 3, also carried out in the South region by Holzmann et al, found that even patients with liver cirrhosis achieved SVR rates ranging from 88.5% to 100% [27] .In another study, in which 219 patients underwent therapy with DAAs, a high rate of SVR and excellent drug tolerability were found.…”
Section: Discussionmentioning
confidence: 99%
“…Another study including 1,002 patients treated for HCV, with genotypes 1, 2 and 3, also carried out in the South region by Holzmann et al, found that even patients with liver cirrhosis achieved SVR rates ranging from 88.5% to 100% [27] .In another study, in which 219 patients underwent therapy with DAAs, a high rate of SVR and excellent drug tolerability were found. Failure to achieve SVR was observed mainly among patients with at least one negative response predictor: cirrhosis and/or genotypes 2 or 3 [16] . Other studies carried out in the Southeast region yielded similar data [18,19,20, 21,29,30] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations